Nostalgiczne kino Wiery Storożewej i Pawła Łungina (na podstawie filmów Podróż ze zwierzętami domowymi i Taxi Blues) - Waligórska-Olejniczak, Beata (Studia Rossica Posnaniensia, 2019)
The article presents the interpretation of two Russian films, Travelling with Pets by Vera Storozheva and Taxi Blues by Pavel Lungin, from the point of view of the category of nostalgia. The article shows that the heroes of both artistic texts function in the hybrid reality, the collapse of the old world accompanies their search for the wholeness and new identity. Travelling with Pets emphasizes the spatial dimension of the experience, whereas Taxi Blues transforms it into the vision of the relationship with time, the continuum of past, present and future, which corresponds with the triad: history-memory-nostalgia.